Indonesia Military Research and Development in Dealing With The Sixth Generation Warfare : The Use of Artificial Intelligence in War Operations - Irvan Arianto Randa Lembang; Romie Oktavianus Bura; R Djoko Andreas Navalino (PT FORMOSA CENDEKIA GLOBAL, 2023)
Technological sophistication brings the world community to be faced with the 6th generation of war, namely war involving the latest technology, artificial intelligence (AI), satellites, and robotics. This indicates that war has gone beyond conventional means, No. longer having to face each other or face to face as happened in the first generation of war. Although in several parts of the world the